2010
DOI: 10.1007/s00340-009-3875-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative gas measurements using a versatile OPO-based cavity ringdown spectrometer and the comparison with spectroscopic databases

Abstract: A versatile OPO-based cavity ringdown spectrometer is reported for quantitative and sensitive gas measurement down to nmol/mol levels. The system is based on cavity ringdown spectroscopy (CRDS) in combination with a continuous wave optical parametric oscillator tunable from 2693 to 3505 nm. Using a single set of CRDS mirrors, spectra were recorded of methane, ethane, benzene, propane, water, acetone and formaldehyde. Gas mixtures were gravimetrically prepared in cylinders or via dynamic generation using diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
(27 reference statements)
0
22
0
2
Order By: Relevance
“…With the current setup, there is no significant difference between the detection limit of the on-axis and the off-axis technique. The detection limit is also of the same order of magnitude as to what has been previously reported for an on-axis CRDS setup based on a mid-infrared cw-OPO [33] or other rather simple CEAS methods, such as optical-feedback cavity-enhanced absorption spectroscopy based on a mid-infrared quantum cascade laser at 4.43 μm [34]. Advantage of a cw-OPO is that it can …”
Section: Performance Of the Spectrometermentioning
confidence: 52%
“…With the current setup, there is no significant difference between the detection limit of the on-axis and the off-axis technique. The detection limit is also of the same order of magnitude as to what has been previously reported for an on-axis CRDS setup based on a mid-infrared cw-OPO [33] or other rather simple CEAS methods, such as optical-feedback cavity-enhanced absorption spectroscopy based on a mid-infrared quantum cascade laser at 4.43 μm [34]. Advantage of a cw-OPO is that it can …”
Section: Performance Of the Spectrometermentioning
confidence: 52%
“…The effective absorption path length can be increased to several kilometres by coupling the mid-infrared beam into an optical cavity formed by highly reflective low-loss mirrors. Highquality dielectric mirrors with reflectivity of better than 0.9998 in the wavelength region 3-5 µm are commercially available [167]. A 1-m long cavity formed by two such mirrors leads to an optical path length of about 5 km -in other words, a photon coupled into the cavity bounces back and forth between the mirrors for 5 km on average, before escaping the cavity.…”
Section: Cavity-enhanced Absorption Spectroscopymentioning
confidence: 99%
“…Typical ring-down times with highly reflective mirrors in the 3-5 µm band are in the order of 10 µs [167]. In practice, the NNEA of a CW mid-infrared CRDspectrometer is 10 -8 -10 -10 cm -1 Hz -1/2 , making this method very useful for the detection and analysis of small concentrations of trace gases [60,167]. As an example, von Basum et al have demonstrated ppt-level detection limit for ethane in air using a CW-OPO at 3.35 µm (NNEA = 1.6×10 -10 cm -1 Hz -1/2 ) [176].…”
Section: Cavity-enhanced Absorption Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Their high efficiency and wide tuning range, which is only limited by the material transparency range, allowed the OPOs to offer highly attractive all-solid laser sources for various applications, especially in the range of wavelengths not covered by usual laser sources. They are very promising for technological applications such as highresolution spectroscopy [1], detection and diagnosis of gas flows [2][3][4], medicine [5,6], and communications systems [7]. They are particularly useful in the IR region (2-20 μm) in which different molecules have their absorption bands and where there is a lack of tunable laser sources.…”
mentioning
confidence: 99%